CORRELATION BETWEEN AGES AND WORK DURATION WITH LOW BACK PAIN INJURY ON EMPLOYEE OF PT JAKARTA INDUSTRIAL ESTATE PULOGADUNG - Hidayah, Nur Yulianti; Silaban, Shintia (Barometer, 2024)
Office workers are a form of work that is at high risk of experiencing complaints or musculoskeletal disorders (MSDs). Low Back Pain (LBP) is one of the most common MSDs problems, many workers experience symptoms of lower back pain while working. LBP disorders have various risk factors, including individual, occupational, and environmental factors. Several employees of PT. JIEP feels pain in the back to the buttocks. These complaints can cause movement and daily activities to be disrupted. This study aims to determine the correlation between age and length of work on LBP complaints among PT. JIEP using the Multiple Linear Regression. Data was obtained by distributing questionnaires to employees of PT. JIEP has 35 people aged 21-30 who work in the HSE, Legal, HCM, IT, Maintenance, and Finance departments. The results of analysis show that the age variable (X1) has no partial relationship to LBP complaints (Y). Whereas in the length of work variable (X2) there is no partial relationship to variable Y. F test states that the variables X1 and X2 together have no relationship with the variable Y which is shown in the F test with a Fcount value of 0.734 <Ftable 3.29. Based on the value of R2 = 0.044, it is known that age and length of work affect LBP complaints by 4.4%. From the results of the questionnaire identifying the factors that cause LBP complaints, it is known that there are two factors, namely work body posture (54.3%) and psychology (45.7%).